2005
DOI: 10.1136/bmj.331.7513.379
|View full text |Cite
|
Sign up to set email alerts
|

Variability in interpretation of chest radiographs among Russian clinicians and implications for screening programmes: observational study

Abstract: Population screening for tuberculosis in Russia may be less than optimal owing to limited agreement on interpretation of chest radiographs, and may have implications for radiological screening programmes in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 15 publications
6
43
2
Order By: Relevance
“…Screening those who are symptomatic may increase yield. Indeed, recent research (in support of older influential research findings) [14] shows that substantial inter-and intraobserver variability occurs in the interpretation of radiographs and a as a test for tuberculosis, a chest radiograph has poor sensitivity and specificity [15]. Furthermore, in England and Wales, .50% of pulmonary tuberculosis occurring in those born abroad may develop within a year of a normal radiograph, supporting the notion that radiographic screening on entry may lack predictive value [12].…”
Section: Discussionmentioning
confidence: 88%
“…Screening those who are symptomatic may increase yield. Indeed, recent research (in support of older influential research findings) [14] shows that substantial inter-and intraobserver variability occurs in the interpretation of radiographs and a as a test for tuberculosis, a chest radiograph has poor sensitivity and specificity [15]. Furthermore, in England and Wales, .50% of pulmonary tuberculosis occurring in those born abroad may develop within a year of a normal radiograph, supporting the notion that radiographic screening on entry may lack predictive value [12].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the detection of these depends on their location, size, and content, and wall thickness. Balabanova et al [10] had found the similar inter-observer agreement between pneumologists and radiologists in Russia.…”
Section: Discussionmentioning
confidence: 70%
“…Abubakar et al [24] observed a moderate agreement for both radiologists and pneumologists. Balabanova et al [10] had reported a poor agreement between pneumologists and moderate between radiologists. However, in our study, the pneumologists because of their specific activities were of risk of "hindsight bias", especially since there were 23/47 cases of PTB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Radiography would detect more active TB cases than the clinical questionnaires that are currently used to discover TB cases in African prisons. 3 Unfortunately, the diagnostic accuracy of CXRs for the detection of active pulmonary TB (PTB) is highly dependent on the reader, 11,12 and health personnel with TB-specific radiology training are scarce in sub-Saharan Africa, especially in the health facilities of penitentiary institutions.…”
mentioning
confidence: 99%